Investigating Neonatal Sepsis: Risk Factors, Incidence, and Mortality in a Hospital Setting - Hussen Salama; Munder Zaied; Faraj Saqar (African Journal of Advanced Pure and Applied Sciences, 2025)
Neonatal sepsis is the main cause of death in neonatal intensive care unit. It is widely spreading in all countries and dividing to tow main groups. There are many risk factors that associated with this medical condition such as, low birth weight, pre maturity, rupture of membrane, prolonged labor, and meconium. In this study, the group of work has designed a plan of work to study neonatal sepsis in Ali Omar Askar hospital . According to the plan , the group of the work has collected data of neonatal sepsis during four months in the hospital in the year of 2022 to assess cases of neonatal sepsis. The results have showed that the neonatal sepsis is usually happening in first 72 hour of life. In addition, the first line Antibiotic is effective in high percentage of neonatal sepsis cases. Furthermore, the rate of death due to neonatal sepsis is 2.4% in incidence. We concluded that the neonatal sepsis death rates is higher than the United States.